Penerimaan Masuk Peguam Syarie Di Malaysia - Sheikh Salim Sheikh Salleh; Abidah Abdul Ghafar; Syahirah Abdul Shukor; Dina Imam Supaat (Universiti Sains Islam Malaysia, 2024)
Legal profession is a reputable profesyen and respectable by the society at large in Malaysia. Legal profession can be divided into t~vo:c ivil lawyers and syarie lawyers. The profession of the syarie lawyers is adn~inistered separately from the profession of civil la\vyers. There is tremendous improvement in the profession of the syarie lawyers as the government put a lot of efforts to upg-ade the Syariah court in Malaysia. Provisions on syarie lanryers are provided under the enactments in every state in Malaysia i.e. the Enactment of Administration of Syariah Courts. In these enactments, it provides the rules of Syarie lalvyers known as Kaeciah-kaeciah Pegtan1 $>ar.ie. Enactments of Administration of Syariah Courts provide the jurisdiction and the powrer for a syarie lawyer to appear and handle the cases in Syariah Courts in Malaysia. The provisions on syarie lawyer differ from one state to another due to the different provisions. This research would like to identify the existing requirements and procedures applicable in each state before a person is qualified to practice as a syariah lawyer in the intended state.